KARAKTERISASI MATERIAL KOMPOSIT DARI LIMBAH PLASTIK, SABUT KELAPA DAN RESIN VINYL ESTER - ADAM MERDEKA (2023)
Sound household waste that is easily decomposed and does not have a considerable enough potential in Indonesia, such as plastic and coconut fiber. The potential for this waste to be generated is sufficient annually. Indonesia's plastic waste reaches 64 million per year, and coconut coir. This study aims to determine the characteristics of raw materials such as coconut coir and HDPE plastic when developed as a composite. Biocomposite is made by combining coconut coir and HDPE plastic with various raw material ratios, then mixed using rheomix at 150°C at 60 rpm. The test method refers to ASTM D368. The resulting tensile strength value is 9.89 MPa - 33.32 MPa. The highest tensile strength value was obtained by varying 25% coconut fiber: 70% HDPE plastic: and 5% vinyl ester resin. The resulting tensile strength value was 33.32 MPa. The elastic modulus value ranges from 1.789 to 3.09 and is directly proportional to the results of the tensile strength value. The FTIR results showed that the resulting biocomposite contained (O-H), O-H (alcohol), C-H alkanes, C-H aldehyde groups, C=O groups, and C-O C=C Alkenes groups. C-H chemical bond, carboxylic acid C-O bond, and C-H Aromatic Ring. Keywords: Coconut coir, FTIR, HDPE plastic, Mechanical properties of biocomposites, and Vinyl ester resin